Meritve tokovnega polja okrog osamljenega mehurja pare nad umetno ustvarjenim zarodnim mestom s tehniko meritve hitrosti s sliko sledilnih delcev - Bašič, Sani (Strojniški vestnik, 2004)
In this paper measurements of the velocity field in the region over a nucleation site that was active during nucleate pool boiling are presented. After the presentation of the principal transport mechanisms in the investigated boiling regime the main aims of the research are defined. The experimental rig is presented and some basic features of the PIV measurement technique are described. A procedure for flow-field measurements is described,the results are presented and we conclude with final statements. Thework contributes to a quantitative determination of the convective effects during the vapour-bubble removal process on heating a wafer after departure from a nucleation site.
Keywords: vrenje mehurčkasto; zakonitosti fizikalne; tehnika merilna; polja tokovna; tokovno polje; vrenje